AC-DC three-phase multipulse converter with boost DC-DC stage and constant hysteresis control - Fernandes, Rodolfo Castanho [UNESP] (2011)
This work proposes a new three-phase multipulse rectifier based on the delta autotransformer connection with DC-DC Boost stages and constant hysteresis control which has the objective of providing a reliable DC bus for on-board applications, electric motor drives and similars, always considering power quality issues. Thus, the proposal presents 0.99 power factor, 6% harmonic distortions in the currents from the mains and enhanced magnetic core utilization, which results in low weight and volume for the overall converter. The proposed control technique uses the simple constant hysteresis concept, thus leading to a low-cost but effective and reliable strategy. © 2011 IEEE.